A COMPARATIVE ANALYSIS OF IMPERIAL JAPAN’S PREDICAMENT IN CHINA AND U.S. QUAGMIRE IN POST-SADDAM IRAQ: SIMILARITIES, LESSONS AND IMPLICATIONS - Matsumura, Masahiro (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
This study will first present a series of striking similarities between the imperial Japanese predicament in China and the contemporary U.S. quagmire in post-Saddam Iraq. Second, the study will provide a theoretical perspective on why the two cases share such commonalities. Third, the study will explore the implications of the perspective to international politics, with a focus on the future of the U.S. hegemony. The study is based on the basic understanding that the developing world across regions today has continued to suffer the ongoing single macro-historical process consequent upon the breakdowns of empires as the once-predominant organizational mode of human societies. The analysis argues for the central importance of a stable national identity for modernization and development as well as freedom and democracy.